The Social Integration of Hindu and Muslim Communities: The Practice of "Menyama-Braya" in Contemporary Bali - Arjawa, I Gst. Pt. Bagus Suka; Zulkifli, Zulkifli (Studia Islamika, 2021)
The social interaction between Bugis Muslims and Hindus in Bali has long been known to be harmonious. This interaction can become a role model for religious interaction in Indonesia. This paper aims to explain the practice of menyama-braya (brotherhood) as a cultural system and its relevance to the integrative social interaction between the Hindu and Bugis Muslim communities in Bali. The research was conducted in the villages of Serangan, Kepaon, Tuban, Suwung, Tanjung Benoa, and Angantiga. The research is qualitative in nature and draws on interviews and the broader literature. The study reveals that a successful harmonious social life cannot be separated from the adoption of menyama-braya culture, which combines the attitude of solidarity and tolerance. The practice of the menyama-braya cultural system has been maintained for generations through various methods, such as socialization, rituals, the use of the same symbols, and formal educational institutions.